(untitled) (Research, Society and Development, 2021)
Botany teaching is debated as a challenge to Biology teachers. Considered a very theoretical approach, Botany is considered a content that is difficult for students to assimilate. The fact is worrying, because in addition to being part of the test in the entrance exams, it is understood the importance of their knowledge in the critical formation of a citizen about their environmental perception. The objective of this study was to evaluate the students’ point of view enrolled in community courses for college entrance examination in Itajubá - MG on the teaching-learning of Botany. The approach adopted to carry out this study was quantitative and qualitative research and the investigation instrument was a questionnaire created using the Google Forms tool. This questionnaire was answered anonymously by 54 students from courses for college entrance examination: Cursinho Assistencial e Centro de Inteligência e Cultura (CACIC), Curso Assistencial Theodomiro Santiago (CATS) and Curso Assistencial Amigos de Itajubá (CAAI), from February 1 to 20, 2021. Although most students are curious about plants, many also declared difficulties in learning the contents of Botany, reflecting a theoretical and content teaching. The students’ view shows the need to make teaching botany more practical and familiar with everyone’s daily life.